BRAVERY IN RICK RIORDAN S THE BLOOD OF OLYMPUS A CHARACTER ANALYSIS - Takaliuang, Thalia; Wuntu, Ceysi Nihta; Sabudu, Delly (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2022)
This research intends to depict Bravery in Rick Riordan s The Blood of Olympus< em> This research is classified as qualitative research because the data are in the form of words rather than numbers The objective approach is used to analyze Rick Riordan s The Blood of Olympus < em>It means that Riordan s work is analyzed in isolation from all these external points of reference analysis as a self sufficient entity constituted because this approach has a relationship with the novel The finding shows that bravery depicted in the novel can be seen through the Discretion of a Piper McLean There also existed the power against bravery and Reyna s mission in combat The novel is one of the literary creations that have real quality Besides that reading a novel is influential for the reader s life because we can understand as well as realize the real condition and life of the story in the novel < p>